2015
DOI: 10.1039/c5ra20722c
|View full text |Cite
|
Sign up to set email alerts
|

Highly dispersible ternary composites with high transparency and ultra low dielectric constants based on hyperbranched polyimide with organosilane termini and cross-linked polyimide with silica

Abstract: Flexible insulating materials that are both thermally and mechanically stable, highly transparent, and have low dielectric constants are highly desirable for electronic applications. With these technical needs, a highly disperse inorganic matrix is the most important factor in polyimide-inorganic composites. We report an optimised method for the preparation of a hyperbranched polyimide using HBPI BPADA-TAP(Si) .This method involves modifying the polymer termini by coupling (3-isocyanatopropyl)triethoxysilane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…37,38 Ando reported the use of the trifunctional organosilicon to prepare low dielectric cross-linked PIs with silica and ever investigated the effects of BATMS-ODPA segment in the cross-linked PIs. 39,40…”
Section: Resultsmentioning
confidence: 99%
“…37,38 Ando reported the use of the trifunctional organosilicon to prepare low dielectric cross-linked PIs with silica and ever investigated the effects of BATMS-ODPA segment in the cross-linked PIs. 39,40…”
Section: Resultsmentioning
confidence: 99%
“…Goto et al prepared a series of PIs with low D k s by introducing bulky diphenyl fluorenylidene moieties and concluded that the D k values of PIs were closely related to the imide group content (Imide%) in the repeating unit and fluorine content (F%). Based on their findings, various PIs with low D k have been reported. Our previous works on low D k PIs also revealed that incorporation of phenylene ether and adamantyl and alicyclic units to dianhydrides and diamines could effectively decrease the D k values of PIs. Most of the above studies focused on the development of PIs with low D k values at lower frequencies (1 kHz to 10 MHz). , However, few studies investigate the molecular structure of PIs with low D k as well as low D f . In particular, there is no clear guideline for designing PIs with both low D k and low D f , which is very important for the emerging 5G mobile communications technology. Therefore, it is of great interest and a challenge to establish the design concept of low D k and low D f PIs.…”
Section: Introductionmentioning
confidence: 99%
“…The authors then terminally modified PI BPADA-TAP(OH) by (3-isocyanatopropyl) triethoxysilane (ICTEOS), and prepared PI 6FDA-APB(Si) -PI BPADA-TAP(Si) /SiO 2 ternary composite film (10 μm thick, SD in Figure 8) by sol-gel method. 120 The connection between terminal-modified PI BPADA-TAP(Si) and siloxane is both chemical bond, which not only makes the dispersion uniformity higher, but also improves the optical and dielectric properties of the material. The λ 0 of SD are 320-323 nm.…”
Section: Introduction Of Silica-based Particlesmentioning
confidence: 99%